From the margins of war to the center of peace-building: How gendered security dynamics matter - Idler, A (Oxford University Press, 2019)
This article argues that unpacking gendered security dynamics helps overcome a binary view of peace and conflict, in scholarship and practice. Drawing on narratives from women and others in the case of Colombia, I show how a gender lens reveals long-term peace-building developments and experiences, and how women start processes that lead to peace, even in the midst of conflict. Therefore, if scholarship is to be conducive to the transformative goal of positive peace, it should shed light on the role of women in, and their perceptions of, security dynamics more widely and shift from focusing on male-dominated power centers to embracing experiences in the margins.